The Distribution of Enjoyment - Todd McGowan (EJP import test, 2021)
Summary: This essay confronts the problem of the enjoyment produced by right-wing populism through a psychoanalytic interpretation of this phenomenon. The structure of right-wing populism is instructive because it enables us to thoroughly disentangle the enjoyment that it produces from power. As a result, we can recognize how the supporters of the populist leader enjoy through the very threat to their identity that the leader promises to eliminate (primarily immigrants). This, in turn, permits a new theorization of the structure of enjoyment as such.
Keywords: Enjoyment; Nation; populism; power; Trump